2016
DOI: 10.1021/acs.analchem.6b02670
|View full text |Cite
|
Sign up to set email alerts
|

Femtomolar Detection of Silver Nanoparticles by Flow-Enhanced Direct-Impact Voltammetry at a Microelectrode Array

Abstract: We report the femtomolar detection of silver (Ag) nanoparticles by direct-impact voltammetry. This is achieved through the use of a random array of microelectrodes (RAM) integrated into a purpose-built flow cell, allowing combined diffusion and convection to the electrode surface. A coupled RAM-flow cell system is implemented and is shown to give reproducible wall-jet type flow characteristics, using potassium ferrocyanide as a molecular redox species. The calibrated flow system is then used to detect and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Nanoparticle collisions at an electrode surface can support direct electron transfer, thereby permitting examination of the heterogeneous electron transfer kinetics of nanoparticles with fast response times and high signal‐to‐noise ratios . A single nanoparticle colliding on the electrode surface can also block the electrode from transferring charge (if the nanoparticle is not redox active), serve as an active‐site for electrocatalytic reaction, or initiate direct redox reactions involving the nanoparticle species . Xiao and Bard first characterized single nanoparticle collisions on an ultramicroelectrode by recording the current transients from electrocatalytic reactions in the presence of nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle collisions at an electrode surface can support direct electron transfer, thereby permitting examination of the heterogeneous electron transfer kinetics of nanoparticles with fast response times and high signal‐to‐noise ratios . A single nanoparticle colliding on the electrode surface can also block the electrode from transferring charge (if the nanoparticle is not redox active), serve as an active‐site for electrocatalytic reaction, or initiate direct redox reactions involving the nanoparticle species . Xiao and Bard first characterized single nanoparticle collisions on an ultramicroelectrode by recording the current transients from electrocatalytic reactions in the presence of nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Femtomolar concentrations of AgNPs have been detected by direct impact voltammetry using a random array of microelectrodes integrated into a flow cell. It was shown that under flow conditions, the impact frequency increases linearly with the flow rate, which enhances mass transport by flow . Some reports show good agreement for nanoparticle size measurements between the collision experiments, electron microscopy and light scattering techniques …”
Section: Analytical Information That Can Be Extracted From Single‐entmentioning
confidence: 99%
“…Electrochemical detection of gold nanoparticles in flow based on more complex reaction path including electrocatalytic reaction was also reported . Electrochemical detection of Ag nanoparticles in flow based on their electrodissolution was also examined . Apart from fundamental aspects , such studies are of practical importance, because of the increasing amounts of nanomaterials released to the environment and their potential toxicity .…”
Section: Introductionmentioning
confidence: 99%